Integration of geoelectric and electromagnetic methods to delineate subsurface mineralization in bostonite rocks, South El-Atshan area, Central Eastern Desert, Egypt - ABDELSALAM, Hussein F.; YOUSEF, Mohamed H. M.; SHAHEEN, Mohamed A.; BADR, Hassan M.; EL-HAWARY, Ali M.; AL-ALFY, Ibrahim M. (Contributions to Geophysics and Geodesy, 2024)
Bostonite rocks are widely spread in the Central Eastern Desert (CED) of Egypt, they are found in the form of sills or dykes injected in the Precambrian rocks. Postgeosynclinal (Hammamat) sediments were intruded by Postorogenic bostonites. The study of this area, using ground geophysical methods, aimed at tracking the radioactive mineralization under the surface, based on the possible association of this radioactive mineralization with some other mineralizations such as sulphides. The application of the self-potential survey shows that the highest negative anomalies are associated with the South El-Atshan bostonite sill and its contact zones. The depths to the centres of some selected anomalies range from 5.7 m to 24 m, half-widths oscillate from 6 to 32 m, with shallow dips towards the west and east directions. The horizontal-loop electromagnetic (HLEM) survey, which was conducted using four frequencies, revealed the presence of two conductive bodies. These conductive bodies possess narrow widths and depths, ranging from 25 m to 27 m, dipping towards the west direction with shallow angles of 25° and 40°, respectively. In addition, the induced polarization (IP) profile shows high chargeability values reaching more than 7.9 mV/V at depths starting from about 10 m to about 35 m. This zone corresponds to a high-resistance zone that may reflect a subsurface disseminated mineralization. The integration of the results obtained using the three techniques makes it possible to determine the most appropriate zones for the development of exploration in the area of investigation.